The use of alternative treatments for Autism Spectrum Disorder - Sander Begeer; Elisa Back; Kim Jonkman (OSF Registries, 2021)
Autism is a heterogeneous condition and treatment options vary. This study will investigate whether differing characteristics/profiles of children with autism are linked to the use of alternative treatments. Alternative treatments are used to treat a variety of other ASD symptoms and comorbid difficulties. There is some evidence that the use of complementary and alternative medicine (CAM) treatments is more common in autism compared to other disorders (Höfer et al., 2017).
The use of alternative treatments is interesting given that these treatments often have no theoretical foundation for their effectiveness and can even be harmful. There are mixed findings about the association between CAM use and sex, age and autism severity in children (Höfer et al., 2017). Overall, higher parental education level has been associated with more CAM use in both autism studies and studies among other populations (Höfer et al., 2017; Wang et al., 2018). Other predictors that have been suggested in non-autism literature include parents who use CAM treatments themselves (Doering et al., 2013; Singendonk et al., 2013), female gender (Keene et al., 2019; Singendonk et al., 2013; Wang et al., 2018), a higher level of education of the patient (Keene et al., 2019; Wang et al., 2018) and a co-occurring medical condition (Wang et al., 2018).

This project will investigate which particular characteristics can predict the use of alternative treatments or subtypes of alternative treatment for autism. Factors that will be explored include: age, sex, ethnicity, intellectual disability, parental education, level of education/current education, age of diagnosis, comorbidity, autism severity and the use of mainstream treatment.
Keywords: Developmental Psychology; Child Psychology; Social and Behavioral Sciences; Psychology; Alternative treatment; Autism